Information System Strategic Planning DPMPTSP Riau Province using Ward and Peppard Method - Sonya Meitarice; Mayang Sari; Meidiana Meidiana; Rosa Adhawiyah; Vira Febriyanti (Sistemasi: Jurnal Sistem Informasi, 2022)
Appropriate application of information systems and information technology can increase efficiency and effectiveness and create a competitive advantage. Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Riau Province is one of the agencies for providing integrated licensing services spread throughout the Provinces and Regencies/Cities in Indonesia. DPMPTSP is required to carry out the task of licensing services that are fast, accurate, in accordance with existing regulations and transparent costs to the entire community. Thus, it is necessary to design a strategic information system so that the implementation of IS/IT is in line with the vision and mission as well as the company's goals. This research uses the Ward and Peppard method because the method has a fairly clear and complete framework besides that it does not only focus on technology, but also focuses on the business needs of the organization. The result of this research are recommendations for future portfolio applications that can be used within the next four years.